2013
DOI: 10.1038/ijo.2013.116
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: PPARδ binding to heme oxygenase 1 promoter prevents angiotensin II-induced adipocyte dysfunction in Goldblatt hypertensive rats

Abstract: Objective:Renin–angiotensin system (RAS) regulates adipogenic response with adipocyte hypertrophy by increasing oxidative stress. Recent studies have shown the role of peroxisome proliferator-activated receptor-δ (PPARδ) agonist in attenuation of angiotensin II-induced oxidative stress. The aim of this study was to explore a potential mechanistic link between PPARδ and the cytoprotective enzyme heme oxygenase-1 (HO-1) and to elucidate the contribution of HO-1 to the adipocyte regulatory effects of PPARδ agonis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 32 publications
(60 reference statements)
4
34
0
Order By: Relevance
“…In addition, over-expression of HO-1 increases pAMPK and eNOS levels and promotes human osteoblastic differentiation, another direction of cell differentiation [293]. It was found that induction of HO-1was associated with reduction of C/EBPα, PPARγ, Peg-1/Mest, aP2, CD36, Wnt5b expression and the increase of β-catenin, pGSK3β, Wnt10b, Pref-1, shh, and adiponectin [280,283,[294][295][296], indicating that those key factors were responsible for HO-exerted effect on adipogenesis.…”
Section: Heme Oxygenase and Adipocyte Differentiationmentioning
confidence: 96%
“…In addition, over-expression of HO-1 increases pAMPK and eNOS levels and promotes human osteoblastic differentiation, another direction of cell differentiation [293]. It was found that induction of HO-1was associated with reduction of C/EBPα, PPARγ, Peg-1/Mest, aP2, CD36, Wnt5b expression and the increase of β-catenin, pGSK3β, Wnt10b, Pref-1, shh, and adiponectin [280,283,[294][295][296], indicating that those key factors were responsible for HO-exerted effect on adipogenesis.…”
Section: Heme Oxygenase and Adipocyte Differentiationmentioning
confidence: 96%
“…Importantly, these attributes of hemin were accompanied by the restoration of adipocyte morphology and improved adipocyte function as evidenced by increased adiponectin levels. Given that hypertriglyceridemia, hypercholesteromia, and excessive pericardial adiposity are major pathophysiological causes of heart failure and related cardiac complications, 8,[43][44][45][46] the suppression of hypertriglyceridemia, hypercholesteromia, and pericardial adiposity in hemin-treated ZFs, and the corresponding decline of adipocyte hypertrophy, TGF-b, osteopontin, pro-inflammatory macrophage M1 phenotype, TNF-a, IL-6, IL-1b, and 8-isoprostane, [22][23][24][25][26][27][28][29][30][31]54,[60][61][62][63] which were associated with the potentiation of the anti-inflammatory macrophage M2 phenotype, proteins of regeneration such as beta-catenin, Oct3/4, and pax2 [32][33][34] are among the multifaceted mechanisms by which the HO system restores adipocyte morphology and improved adipocyte function. Moreover, the effect of the HO system on the expression of proteins of regeneration such as Oct3/4 and pax2 is a novel mechanism unveiled by this study through which hemin may restore adipocyte morphology and function.…”
Section: Discussionmentioning
confidence: 99%
“…To investigate the mechanisms by which hemin improves pericardial adipocyte morphology, we measured the expression of proteins of regeneration such as beta-catenin, Oct3/4, and pax2 [32][33][34] in the adipose tissue. Our results indicate that the expressions of beta-catenin, Oct3/4, and pax2 in ZFs were significantly reduced as compared to the ZL control (Figure 7(a) to (c)).…”
Section: Hemin Administration Enhanced Proteins Of Regeneration In Thmentioning
confidence: 99%
See 1 more Smart Citation
“…It is not surprising because oxidative related process such as oxidative stress is associated with adiposity caused by VAT accumulation [42,43]. In fact, as two important oxidant genes of oxidative stress, the expression levels of p47phox and GP91-PHOX were shown to be positively associated with VAT mass in mice or rats [43,44], suggesting VAT changes resulted in oxidative stress by regulating the expression of p47phox and GP91-PHOX. For antioxidant markers, oxidative stress reduced the levels of GPX3 in the plasma of obese subjects and adipose tissue of HFD mice [45,46] as well as GSTA4 expression in adipose tissue of obese C57BL/6J mice [47].…”
Section: Discussionmentioning
confidence: 99%